2010
DOI: 10.1016/j.ejso.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

‘Close Shave’ in liver resection for colorectal liver metastases

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D ARTICLE IN PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The inability to obtain tumor-free margins is considered a contraindication for surgical resection because R1 (microscopic positive margin) or R2 (macroscopic positive margin) resections are associated with high local recurrence and poor survival rates. Although complete tumor removal is currently the gold standard for surgical treatment of CRLM, the optimal width or magnitude of the resection margin remains controversial, especially in the era of chemotherapeutic treatment modalities [3,[17][18][19][20]. Most patients with CRLM are not candidates for hepatic resection due to anatomic limitations, the multifocal nature of the disease, inadequate functional liver reserve, unresectable extrahepatic metastases, or medical comorbidities.…”
Section: Discussionmentioning
confidence: 97%
“…The inability to obtain tumor-free margins is considered a contraindication for surgical resection because R1 (microscopic positive margin) or R2 (macroscopic positive margin) resections are associated with high local recurrence and poor survival rates. Although complete tumor removal is currently the gold standard for surgical treatment of CRLM, the optimal width or magnitude of the resection margin remains controversial, especially in the era of chemotherapeutic treatment modalities [3,[17][18][19][20]. Most patients with CRLM are not candidates for hepatic resection due to anatomic limitations, the multifocal nature of the disease, inadequate functional liver reserve, unresectable extrahepatic metastases, or medical comorbidities.…”
Section: Discussionmentioning
confidence: 97%
“…Current data do not support planning for surgical resection with foreknowledge that residual disease will be left behind. 36 Stereotactic radiotherapy of the liver has a firm role both as an adjunct to surgical resection and in the management of patients who are not surgical candidates. In our consecutive cohort of patients with liver-limited unresectable oligometastases of the liver or primary hepatocellular carcinoma, SABR provided excellent sustained local control.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to effective systemic therapy, studies identified a survival advantage when a negative margin width of 1 cm was achieved and a consensus developed that this margin width was not only optimal, but defined resectability . Recent studies that include patients treated with pre‐operative systemic therapy, consistently have found that the resection margin width, as long as no tumour cells are microscopically present at the margin, does not impact long‐term survival . Two recent detailed analyses provide the genetic and pathological bases for this argument …”
Section: Definition Of Resectabilitymentioning
confidence: 99%